Teacher Empowerment in the Implementation of Low Carbon Education to Increase Students' Environmental Awareness - Probosari, Riezky Maya; Hudha, Muhammad Nur; Wati, Icha Kurnia; Khasanah, Annisa Nur; Supurwoko, Supurwoko (Teaching, Learning, and Development, 2025)
Environmental problems due to excessive carbon emissions are increasing, while student awareness of this issue is still low. Science learning has great potential in instilling sustainability values. Therefore, this service aims to empower teachers in one of the junior high schools in Central Java in designing and implementing Low Carbon Education (LCE) based learning. The short-term goal of this activity is to improve teachers' understanding of the concept of low carbon and its application in learning. In the long term, teachers are expected to be able to develop learning innovations that are more contextualized and can apply students' low carbon lifestyle in their daily lives. The methods used include socialization of the LCE concept, development of low carbon-based learning tools, implementation in the form of simple experiments and environmental projects, and program evaluation. The results show an increase in teachers' understanding of LCE and the emergence of applicable environment-based learning projects. The main contribution of this program is the availability of a model for teacher capacity building in implementing LCE that can be replicated in other education units, while contributing to climate change mitigation efforts through education.